2022
DOI: 10.3390/su14106034
|View full text |Cite
|
Sign up to set email alerts
|

The Tripartite Evolution Game of Environmental Governance under the Intervention of Central Government

Abstract: Environmental pollution management is about the sustainable development effects of enterprises and the quality of life of people. However, the frequent occurrence of various types of enterprises polluting the environment in recent years has revealed many problems, such as the lack of monitoring by relevant central agencies, the ineffective supervision by local governments, and the failure of public complaints. This paper considers the rent-seeking phenomenon of enterprises in pollution prevention and control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The studies of Dasgupta et al, which are based on samples of developing countries such as Argentina, Chile, and Mexico, showed that the disclosure of an enterprise's environmental pollution incident by the media exerts an impact on that enterprise's performance in the capital market, thereby inhibiting enterprises' environmental behavior (82). Gupta and Goldar reached similar conclusions based on research in India (83).…”
Section: The Role Of the Mediamentioning
confidence: 89%
“…The studies of Dasgupta et al, which are based on samples of developing countries such as Argentina, Chile, and Mexico, showed that the disclosure of an enterprise's environmental pollution incident by the media exerts an impact on that enterprise's performance in the capital market, thereby inhibiting enterprises' environmental behavior (82). Gupta and Goldar reached similar conclusions based on research in India (83).…”
Section: The Role Of the Mediamentioning
confidence: 89%
“…Finally, we will improve the environmental tax incentive mechanism that forces enterprises to go green. The environmental protection tax is an important part of greening the tax system [65]. The environmental protection tax should be introduced as a precursor to gradually adjust the structure of the environmental protection tax system, improve the environmental protection tax system, improve the transparency of taxation, and implement the government penalties along with the government subsidy incentives to help enterprises achieve green upgrading.…”
Section: Discussionmentioning
confidence: 99%
“…Yi Shi et al used evolutionary game theory to analyze the influence of three different environmental regulations on enterprise green science and technology innovation and finally found that combined environmental regulation is beneficial to the development of enterprise technological innovation [34]. According to the rent-seeking phenomenon of enterprises in pollution prevention and control, Zhu et al constructed a tripartite evolutionary game model among enterprises, local governments, and the central government and finally found that the government reward strategy is helpful to the choice of enterprise strategy in an ideal state [35].…”
Section: Related Literaturementioning
confidence: 99%